2019
DOI: 10.3389/fped.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Index as a Predictor of Mortality in Pediatric Patients With Solid Tumors

Abstract: Purpose: The objective of this study was to determine whether a comorbidity index could be used to predict mortality in pediatric patients with chemotherapy-treated solid tumors. Methods: Pediatric patients who underwent chemotherapy treatment for solid tumors were included, and demographic, clinical, and comorbidity data were obtained from patient electronic records. Results: A total of 196 pediatric patients with embryonic solid tumors were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…For patients recruited from adult centers, the iHCP determined if patients had high unmet health or social needs as defined by Schaink et al [ 36 ]. Although a Pediatric Comorbidity Index is being developed, there is currently no validated measure of comorbidity or complexity for pediatric patients [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…For patients recruited from adult centers, the iHCP determined if patients had high unmet health or social needs as defined by Schaink et al [ 36 ]. Although a Pediatric Comorbidity Index is being developed, there is currently no validated measure of comorbidity or complexity for pediatric patients [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ECI was applied for measuring patient comorbidities which, like Charlson Comorbidity Index (CCI) [ 47 ] is validated for adult populations. Although studies of T1D generally involve a higher prevalence of pediatric patients, and other studies [ 48 ] have shown that pediatric-specific comorbidity indices perform most optimally among these groups, this study population largely comprised adults. Lastly, because of the pandemic, many patients avoided hospital visits [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study used the most recent available recordings of SEIFA, IRSEO, ARIA, age and jurisdiction of residence for each individual. As comorbidity indices such as the Charlson Comorbidity Index [ 24 ] are not suitable for childhood conditions [ 25 ], individual comorbidities based on ICD-10-AM coded hospital admissions were investigated. The comorbidities included chronic obstructive pulmonary diseases, chronic kidney disease, other cardiovascular diseases, coronary heart disease, anticoagulant treatment, diabetes and mental health conditions.…”
Section: Methodsmentioning
confidence: 99%